Pembinaan Pola Hidup Sehat Berbasis Olahraga di Desa Wisata Kampung Emas Yogyakarta - Wijaya, Ridho Gata; Kriswanto, Erwin Setyo; Prayadi, Heri Yogo; Mayang Fitri, Ebtana Sella; Wijaya, Krisna (Jurnal Dharma Bhakti Ekuitas, 2024)
A few years earlier, the world was going through a critical period due to the outbreak of the Covid-19 pandemic. This outbreak then changed its status from a pandemic to an endemic, people must continue to maintain their own health, including in a healthy lifestyle in their daily lives. This service focuses on implementing community service programs that focus on the goal of fostering a healthy lifestyle for the younger generation in Krapyak village, Sleman regency. The assessment methods used in this community service program are lecture, observation, and demonstration methods. The target object of this service is the community and young people of the tourist village of Kampung Emas Yogyakarta. The result of this program is the implementation of sports-based healthy lifestyle workshops for the younger generation and figures in the village which are then optimized with sports mentoring activities in order to understand and familiarize a healthy lifestyle for the younger generation in Krapyak village through physical activity. The coaching of sports activities carried out is badminton, table tennis, archery, mini soccer, pencak silat, outbound, and gymnastics. The implementation of this service received a positive response from the community where the service was served. In the future, service can be done again by further activating the youth element of the village cadets who can act as service partners and maintain the continuity of the coaching program at all times. Keywords: Coaching, golden village, health., healthy lifestyle, sport-tourism. Abstrak Beberapa tahun sebelumnya, kondisi dunia yang sedang melewati masa-masa kritis akibat pandemi Covid-19. Wabah ini kemudian berubah statusnya dari pandemi menjadi sebuah endemi, masyarakat harus tetap menjaga kesehatan dirinya masing-masing, termasuk dalam pola hidup sehat di kehidupannya sehari-hari. Pengabdian ini berfokus pada pelaksanaan program pengabdian kepada masyarakat yang fokus pada tujuan untuk pembinaan pola hidup sehat para generasi muda di desa Krapyak wilayah kabupaten Sleman. Adapun metode pengkajian yang digunakan dalam program pengabdian masyarakat ini adalah metode ceramah, observasi, dan demonstrasi. Adapun sasaran objek pengabdian ini adalah masyarakat dan anak-anak muda desa wisata Kampung Emas Yogyakarta. Hasil kegiatan dari program ini adalah dilaksanakannya kegiatan workshop pola hidup sehat berbasis olahraga pada generasi muda dan tokoh-tokoh di desa yang kemudian dioptimalkan dengan kegiatan pendampingan olahraga dalam rangka meningkatkan pemahaman sekaligus membiasakan pola hidup sehat bagi generasi muda di desa Krapyak melalui aktivitas fisik. Adapun pembinaan kegiatan olahraga yang dilaksanakan adalah bulu tangkis, tenis meja, panahan, mini soccer, pencak silat, outbond, dan senam. Pelaksanaan pengabdian ini mendapat respon positif dari masyarakat tempat pengabdian. Kedepannya, pengabdian bisa dilakukan lagi dengan lebih mengaktifkan elemen pemuda karang taruna desa yang bisa berperan sebagai rekan pengabdian dan menjaga keberlangsungan program pembinaan setiap waktunya. Kata kunci: Pembinaan, kampung emas, kesehatan, pola hidup sehat, sport-tourism.